Fintech Solutions in Shaping Capital Structure under Conditions of Intensified Uncertainty at Micro and Macro Levels - Aleksin Glib O.; Usherenko Svitlana V.; Gryshchuk Andrii S.; Kosko Oleksandr V. (Bìznes Inform, 2025)
In the context of increasing uncertainty at both micro and macro levels caused by exogenous and endogenous crises, the significance of making strategic decisions in corporate finance, particularly regarding the optimization of capital structure, is heightened. The aim of this article is to analyze the features of capital structure formation influenced by fintech solutions in the context of growing uncertainty from both theoretical and empirical perspectives. The article examines both the theoretical and practical aspects of the impact of fintech solutions on the formation of enterprises’ capital structures in conditions of intensified uncertainty. It is substantiated that fintech technologies, including blockchain, RegTech, compliance digital platforms, and smart contracts, contribute to reducing information asymmetry, enhancing transparency, and increasing institutional trust, which lowers risk premiums and reduces the cost of capital. It is emphasized that the use of crowdfunding tools, P2P lending, asset tokenization, and DeFi platforms creates alternative sources of financing, which is particularly important for small and medium-sized enterprises in conditions of limited access to traditional bank lending. The analysis indicates that fintech contributes to the diversification of sources of capital, the reduction of transaction costs, and the increase of financial flexibility of enterprises. Empirical data indicate that the cost of capital for enterprises that implement fintech solutions is lower compared to companies that rely exclusively on traditional financing. It is determined that fintech is a key factor in adapting corporate finance to conditions of high volatility and transforming market conditions, forming a new paradigm of strategic management of capital structure. Further research will focus on the analysis of the role of fintech solutions in ensuring the effectiveness of management decisions in the corporate sector under the conditions of wartime and post-war economy of Ukraine.